ҚАРАҚАЛПАҚ ГҮРРИҢЛЕРИНИҢ ИЗЕРТЛЕНИЎ ТАРИЙХЫНАН - Ктайбекова, З.К. (SCIENCE and SOCIETY, 2017)
This article of narration investigation history especially period of vient present epoch of Karakalpak stories to learn history of literature science the very culmination problem. History of literature is well-know stories of investigation scientist M.Nurmuhammedov, S.Bahadirova, A.Amanova, P.Allambergenova’s viewpoint basic of science.
Keywords: epic genre; stories; themes; research; skill; prose